FAKTOR RISIKO KEJADIAN STROKE - Mevi Lilipory; Moren Lilipory (Lembaga Penerbitan Fakultas Kesehatan Universitas Kristen Indonesia Maluku, 2021)
Stroke is a global epidemic problem that threatens life, health and quality of life. Stroke as a major problem for public health because it is the cause of a lot of pain, disability, and death. The study aims of this observation is to determine the risk factors for stroke in the Hutumuri Public Health Center year 2020. This observation uses quantitative research with a case control research design using a retrospective approach. The sample of this study were 64 people with a ratio of 1: 1 (32 cases and 32 controls). The results of this study found that the risk factors for stroke were hypertension (p = 0.00; OR = 8.52; 95% CI 2.15 - 33.78), diet (p = 0.77; OR = 2.82; 95% CI 1, 01-7.76), while Physical Activity (p = 1.00; OR = 0.80; 95% CI 0.21 - 2.95) was not proven as a significant risk factor for stroke. Hypertension and Dietary habit are Risk Factors for Stroke Occurrence at the Hutumuri Public Health Center year 2020. Therefore expected to prevent it with controlling blood pressure and maintaining dietary habit Keywords: Hypertension, Dietary habit, Physical Activity, Stroke